2015
DOI: 10.1007/s12031-015-0670-y
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyeicosanoid Signaling Provides Multi-target Protective Effects on Neurovascular Unit in Rats After Focal Ischemia

Abstract: Multiple players are involved in the highly complex pathophysiologic responses after stroke. Therefore, therapeutic approaches that target multiple cellular elements of the neurovascular unit in the damage cascade hold considerable promise for the treatment of stroke. Cytochrome P450 (CYP) epoxygenases metabolize arachidonic acid to biologically active eicosanoids called epoxyeicosatrienoic acids (EETs), which are further converted by soluble epoxide hydrolase (sEH) to less bioactive diols. EETs have been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
6
30
0
Order By: Relevance
“…While EDP has some bioactivities similar to those of EET, and in some cases demonstrating greater potencies such as in vasodilation75, opposite biological outcomes have also been observed. For example, EDP has been reported to be anti-angiogenic whereas EET is likely to be pro-angiogenic depending on the specific experimental context40437677. In the present study we showed a similar potency for EET and EDP to reduce in vitro leukocyte adhesion and leukostasis in the mouse.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…While EDP has some bioactivities similar to those of EET, and in some cases demonstrating greater potencies such as in vasodilation75, opposite biological outcomes have also been observed. For example, EDP has been reported to be anti-angiogenic whereas EET is likely to be pro-angiogenic depending on the specific experimental context40437677. In the present study we showed a similar potency for EET and EDP to reduce in vitro leukocyte adhesion and leukostasis in the mouse.…”
Section: Discussionsupporting
confidence: 72%
“…HRMEC cultures were treated with TNFα in the presence or absence of exogenous 11,12-EET, 19,20-EDP, AUDA, or the EET and EDP diols, 11,12-DHET and 19,20-DHDP and VCAM1 and ICAM1 expression was assessed. The concentrations of the epoxides (0.5 μM) or the sEH inhibitor AUDA (10 μM) were determined from preliminary studies and fall within typical ranges used in the literature273940414243. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous papers showed that EETs had anti‐oxidative (Yang et al, ), anti‐inflammatory (Imig, ), anti‐apoptotic (Yang et al, ), vasodilatory (Ellis, Amruthesh, Police, & Yancey, ), angiogenic (Zhang & Harder, ), fibrinolyic (Node et al, ) and anti‐thrombotic (Heizer, McKinney, & Ellis, ) effects. In addition, the epoxyeicosanoid signaling worked protectively on NVU in rat ischemic model (Liu et al, ). We speculated that EETs might be the target of neuroprotective effect of SMTP‐44D.…”
Section: Discussionmentioning
confidence: 99%
“…Older studies for the most part have demonstrated the neuroprotective effect of sEH inhibition in rodent models of ischemic stroke when delivered before or at the onset of ischemia (Dorrance et al, 2005; Liu et al, 2016; Shaik et al, 2013; Simpkins et al, 2009), and one study in mice documented the effectiveness of sEH inhibition given at reperfusion (Zhang et al, 2007). Recent results using a newer generation sEH inhibitor, 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl)urea (TPPU), with higher potency and longer-circulatory half-life, offers support for the clinical relevance of sEH inhibitors to treat ischemic stroke.…”
Section: Recently Identified Molecular/cellular Targets and Approachesmentioning
confidence: 99%